2012
DOI: 10.1186/1471-2474-13-161
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament (ACL) reconstruction with quadriceps tendon autograft and press-fit fixation using an anteromedial portal technique

Abstract: BackgroundThis article describes an arthroscopic anterior cruciate ligament (ACL) reconstruction technique with a quadriceps tendon autograft using an anteromedial portal technique.MethodsA 5 cm quadriceps tendon graft is harvested with an adjacent 2 cm bone block. The femoral tunnel is created through a low anteromedial portal in its anatomical position. The tibial tunnel is created with a hollow burr, thus acquiring a free cylindrical bone block. The graft is then passed through the tibial tunnel and the bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 15 publications
0
45
2
Order By: Relevance
“…• Four relevant [3][4][5][6] studies met the inclusion criteria and were included (based on levels on levels of evidence, Centre for Evidence Based Medicine, 2009).…”
Section: Results Of Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…• Four relevant [3][4][5][6] studies met the inclusion criteria and were included (based on levels on levels of evidence, Centre for Evidence Based Medicine, 2009).…”
Section: Results Of Searchmentioning
confidence: 99%
“…Three Injured knee: of the four studies 3,4,6 reported improvements in outcomes following ACLR using the QTBP graft; one study 5 reported comparable postoperative scores but did not include preoperative values to make direct comparisons.…”
Section: Results Of Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…T he quadriceps tendon (QT) as a graft source for anterior cruciate ligament (ACL) [1][2][3][4][5] and posterior cruciate ligament (PCL) 6 reconstruction has recently achieved increased attention. Although many knee surgeons have been using the QT as a graft for ACL revision surgery, 7,8 it has never gained universal acceptance for primary ACL reconstruction.…”
mentioning
confidence: 99%